Single-agent rituximab and ultra-low-dose adaptive radiotherapy for the treatment of indolent B-cell non-Hodgkin lymphomas - Lake, Katherine E.; Jackson, Meredith; Hull, Samantha; All, Sean; Patel, Akshat M.; Li, Xingzhe; Desai, Neil B.; Yilmaz, Elif; Wolfe, Heather; Zahid, Mohammad Faizan; Li, Hsiao-Ching; Awan, Farrukh; et al. (Frontiers in Oncology, 2025)
IntroductionFor indolent B-cell non-Hodgkin lymphomas (iNHLs), ultra-low-dose radiation therapy (ULDRT) with 4 Gy has demonstrated durable local control (70%), although distal relapses may occur. Concurrent systemic chemotherapy with radiation therapy (RT) extends progression-free survival (PFS) but is often avoided due to toxicity. We hypothesize that the combination of adaptive ULDRT, with repeat treatment as needed, and single-agent rituximab results in excellent local and systemic control with minimal toxicity.MethodsWe conducted an institutional review board (IRB)-approved retrospective review of patients with iNHLs (n=26) who were treated with both ULDRT and rituximab (four weekly doses of 375 mg/m2), either concurrently or within a short interval (median 16 days), at our institution from 2017 to 2024. Treatment response and disease control (local and distant) were measured by PET/CT. Overall survival (OS) and PFS were analyzed using the Kaplan-Meier method. Common Terminology Criteria for Adverse Events (CTCAE) v4 was used to record acute and long-term toxicities.ResultsOverall response rate (ORR) at the first follow-up was 28/31 (90%), of which 19 sites (61%) achieved complete response (CR) and nine (26%) achieved partial response (PR). One (3%) patient had stable disease (SD). In our cohort, the 2-year in-field, out-of-field, and overall PFS rates were 91%, 78%, and 78%, respectively, and OS was 92%. No patient had disease transformation.DiscussionThe combination of rituximab and ULDRT demonstrates sustained local and distant disease control with minimal side effects in iNHLs.